Working Capital Behavior of Firms during an Economic Downturn: An Analysis of the Financial Crisis Era - Hofmann Erik; Töyli Juuso; Solakivi Tomi (MDPI, 2022)
In times of crisis, cash and liquidity play an essential role. This paper analyzes the working capital measures over the course of a business cycle. We examine (1) how companies behave in economic downturns regarding their working capital components and (2) whether firms with higher financial constraints behave differently in economic downturns regarding their working capital components. The analyses were conducted with descriptive statistics and generalized linear mixed-effects modeling. Our dataset consists of 2111 stock-listed firms and 10,555 observations spread over the period of five years during the financial crisis era. The findings indicate that days sales outstanding and shorter days inventory held are related to better financial performance while days payable outstanding had no observable effect. Furthermore, financially constrained firms have shorter days sales outstanding than average firms. In economic downturns, firms seem to reduce both working capital and fixed investments to asset ratios. The financially constrained firms pushed down their fixed investments ratio more aggressively than average firms while, in contrast, the financially strongest firms pushed down the working capital to asset ratio in comparison to average firms. Interestingly, neither the cash conversion cycle, days payable outstanding, nor company performance or fixed investments to asset ratios fully returned to the pre-shock level. The behavior of non-financially constrained firms, which also perform better, indicates a stronger supply chain orientation than that of average firms. This might indicate that the supply chain-oriented view of working capital management could provide a more favorable and resilient alternative to the prevailing self-orientation.